(untitled) (Research, Society and Development, 2021)
Abdominal obesity is associated with an exponential increase in the risk of morbidity and mortality, since the pattern of body fat distribution is the most significant risk factor in morbid processes than generalized obesity. Estimate the prevalence of abdominal obesity and identify the associated factors. Pilot, descriptive cross-sectional study with a quantitative approach. The convenience sample consisted of 50 individuals aged 18 to 50 years. Initially, an anthropometric assessment of the participants was carried out and then a questionnaire was applied to define the profile and habits of the population with altered waist circumference (≥ 88 cm for women or ≥ 102 cm for men). The data were analyzed using descriptive statistics and linear regression using the Epi Info™ software. Among the participants, 58% (n = 29) had abdominal obesity. The variables that showed significance (p-value ≤ 0.05) with abdominal obesity were: being married, not being white, having 8 or more years of schooling; having BMI indicative of overweight and generalized obesity and not consuming alcoholic beverages. Abdominal obesity, as well as generalized obesity, constitutes a major challenge to be addressed by health professionals, considering that a significant fraction of the population is in this circumstance. In this perspective, the prevention and control of abdominal obesity should provide actions that assist individuals in adopting a healthy lifestyle.